The Effect of Ion-Beam Bombardment on Solution-Processed Nickel Oxide Films Used for Liquid Crystal Alignment. (1st January 2019) - Jeong, Hae-Chang; Won, Jonghoon; Lee, Ju Hwan; Kim, Dong Hyun; Lee, Dong Wook; Lee, Yun-Gun; Oh, Byeong Yun; Han, Jeong min; Seo, Dae-Shik
Abstract : We induced a homogeneous liquid crystal (LC) alignment state on ion-beam (IB)-irradiated NiO films fabricated via solution-processing. A topographical analysis was performed using field emission-scanning electron microscopy of the films after various annealing temperatures. After IB irradiation, the surface of the NiO films was rough irrespective of annealing temperature. IB-irradiated NiO films exhibited slightly reduced transparency in the visible region compared to as-deposited NiO film. Moreover, the IB-irradiated NiO films fabricated at the lowest annealing temperature of 100°C exhibited uniform homogeneous LC alignment caused by microgroove-like topographic modification and chemical modification of the NiO surface by the IB irradiation. The pretilt angle of the LC molecules on IB-irradiated NiO film annealed at 100, 200, 300, and 400°C were on average 0.02 0.05, 0.43, and 0.05 o, respectively, making IB-irradiated NiO film eminently suitable for LC alignment.